Case report on laparoscopic management of congenital peritoneal encapsulation: A rare cause of small bowel obstruction - Sumanta Dey; Sreetama Roy; Abhishek Guhathakurta; Debarchan Ghosh (Journal of Minimal Access Surgery)
Peritoneal encapsulation (PE) is a rare congenital disorder described as an accessory peritoneal lining covering a part or whole of the small bowel. Some theorise the encapsulation is due to the formation of adhesion between the physiological hernia and the caudal duodenum. While others have stated it is a defect in the reduction of the physiological hernia. Patients usually present at different stages of intestinal obstruction at any point of time during life. There are also reports on post-humous diagnosis on autopsy. PE is a rare surgical entity, hence not much evidences are available on how to tackle this condition by minimally invasive approach. Here, we report a case of PE in a 43-year-old male who presented with features of intermittent sub-acute intestinal obstruction and was managed by laparoscopic surgery at our institute.